Evaluating consistency of resistance reactions of openpollinated maize cultivars to Striga hermonthica (Del.) Benth under artificial infestation - Menkir, A.; Franco, J.; Adepoju, A.; Bossey, B. (Wiley, 2012)
Striga hermonthica (Del.) Benth is a destructive parasitic weed to maize (Zea mays L.) in West and Central Africa. The presence of large genetic variation among parasite populations contributes to significant genotype × environment interaction, complicating assessment of resistance reactions of genotypes in field trails. The present study was conducted at Abuja and Mokwa in Nigeria for 5 and 6 yr, respectively, with and without artificial Striga infestation (i) to examine the reaction patterns of open-pollinated maize cultivars with varying levels of resistance to S. hermonthica and (ii) to identify cultivars or genotypes with stable resistance to the parasite across varying growing environments. In the combined analysis of variance, cultivar and cultivar × environment interaction significantly affected grain yield, emerged Striga plant count, and Striga damage rating under Striga infested condition. The nonparametric test of concordance was significant (p < 0.0001) and strong (coefficient of concordance [W] = 0.71 to 0.83) for the three traits recorded under infestation, indicating consistent ranking of the resistance reactions of the cultivars to S. hermonthica across environments. Both additive main effects and multiplicative interaction (AMMI) and cluster analyses of each trait recorded under infestation across environments placed the resistant cultivars in one group and the tolerant and susceptible cultivars in a second group. Further analysis of stability of rank order of individual cultivars across environments using nonparametric tests did not indicate any instability of the resistance reactions of the eight open-pollinated maize cultivars. The resistant cultivars had low average ranks for grain yield under infestation, Striga damage rating, and emerged Striga plant count whereas the reverse was true for both the tolerant and susceptible cultivars. Cultivars with stable resistance, which can be used directly for cultivation or as sources of resistance alleles for breeding, were identified in this study.